Творчість та культура в документах ЄС - Найдич, Марина Анатоліївна; Najdych, M. A. (Одеський національний економічний університет, 2012)
У статті йдеться про важливий внесок культури та творчості у суспільне життя, здатність зазначеної галузі впливати не лише на духовний але і на економічний розвиток Європейського Союзу. Розглянуто основні документи та програми, що стосуються розвитку культури та творчості в держав-учасниць ЄС та третіх країн. The article describes the important contribution of culture and creativity in public life, the ability of this industry to influence not only spiritual but also the economic development of European Union citizens and associations in general. The basic documents and programs relating to the development of culture and creativity in the EU member states and third countries were considered.
Creativity and culture as important directions of a European youth policy.
Keywords: культура; творчість; культурна політика ЄС; соціальний та економічний розвиток; culture; creativity; European cultural policy; social and economic development